(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Household energy use accounts for one-third of worldwide primary energy demand, and has a considerable impact on the environment and human health. This study investigated the household energy consumption situation in Gombe Metropolis, Gombe State, Nigeria. The study used a mix of quantitative and qualitative research methods concurrently. Four hundred households were selected using systematic sampling technique. Questionnaire and Key Informant Interviews (KII) were used to collect data, while secondary data was obtained from the Gombe State Bureau of Statistics. Descriptive statistics was used to analyzed the quantitative data while thematic approach was used in qualitative data analysis. Result revealed that the majority of respondents obtained energy for domestic cooking from hydrocarbon sources, which are charcoal (33.2%) fuelwood (27.5%) and liquefied petroleum gas (22.9%) of the energy mix while 76.5% of respondents used a mixed of traditional (charcoal/fuelwood) and modern (LPG) energy sources. Similarly, result from the KII revealed that households in Gombe Metropolis rely heavily on traditional energy sources, such as fuelwood and charcoal, for cooking because of its affordability and availability. The choice of cooking fuel is influenced by factors such as affordability, household size, availability, and accessibility. The study recommended that Regular awareness campaigns through the media and public gatherings should be conducted to emphasize the significance of utilizing modern energy systems for domestic cooking. These efforts will encourage individuals in the study area to move away from heavily relying on hydrocarbon-based fuels towards cleaner and more sustainable energy sources.